Improper Inhalation Technique-A Barrier to Good Asthma Control (Faridpur Medical College Journal, 2011)
Bronchial Asthma (BA) is a chronic airway disorder with significant morbidity and mortality but due to recent advances in the field of medicine most patients with BA can have complete symptom control and live a normal life. There are various routs of drug delivery for asthma control but among them aerosol inhalation is considered the optimal route. A number of pressured Metered Dose Inhalers (MDI) & Dry Powder Inhalers (DPI) are available for this purpose. However inhalation of therapeutic aerosols is not without difficulty, it requires precise instructions on the inhaler maneuvers, which is different from spontaneous normal breathing. Also, the characteristics of the inhaler device have to be suitable for the user. Available data indicate that, lack of knowledge demonstrated by health professionals & patients on the inhalation maneuvers & handling of inhalers resulting in a reduction of therapeutic benefit. The paper reviews the literature concerning the fundamental aspects of inhaler devices, inhalation maneuvers & device selection, in an attempt to increase the knowledge of and to optimize the clinical use of therapeutic inhalers. As a result of which Asthmatics can be kept under good control. Key words: Bronchial Asthma; MDI; DPI; Inhalation technique; Rotahaler; Cozyhaler. DOI: http://dx.doi.org/10.3329/fmcj.v6i2.9212 FMCJ 2011; 6(2): 104-106